Analyzing the Energy Consumption and Economic Growth Nexus in Nigeria - Okoye, Lawrence U.; Omankhanlen, Alexander E.; Okoh, Johnson I.; Adeleye, Ngozi B.; Ezeji, Felix N.; Ezu, Gideon K.; Ehikioya, Benjamin I. (International Journal of Energy Economics and Policy, 2020)
Public and private sectors across the globe formulate and implement policies that target growth of their operations. It is of essence therefore that economic managers and other stakeholders identify and engage key factors that promote economic activities in policy formulation. The connection between economic performance and energy utilization is acknowledged in the literature, but empirics on the nature of this relationship produce mixed outcomes thereby suggesting the need for more research. Using the auto-regressive distributed lag method, this study estimates the effect of energy consumption on economic growth in Nigeria between 1981 and 2017, incorporating financial development, gross fixed capital formation and inflation for enhanced robustness. The results indicate that energy consumption and gross fixed capital formation (proxy for infrastructure) significantly determine growth of economic activities in Nigeria. The study also presents empirical support for delayed response of an endogenous variable to its own shocks as well as shocks to explanatory variables. It therefore asserts that energy consumption is a major determinant of economic growth in Nigeria, and aligns with the energy-led hypothesis. The observed positive impact electricity and capital consumption provides empirical support for the endogenous growth theory. Increased government and private sector investment in energy and infrastructural development is strongly advocated. Keywords: Energy economics, economic growth, energy utilization, endogenous growth, infrastructure. JEL Classifications: C22, O4, O47, Q43 DOI: https://doi.org/10.32479/ijeep.10768